Residual stresses in welded high-strength steel I-Beams. (April 2020) - Le, Tuan; Paradowska, Anna; Bradford, Mark A.; Liu, Xinpei; Valipour, Hamid R.
Abstract: This study investigates a unified residual stress model applicable for welded high-strength steel (HSS) I-beams. In the experimental program, the homogeneous specimens including two prismatic I-beam samples and a web-tapered I-beam fabricated from Australian BISPLATE-80 and BISPLATE-100 steel plates having nominal yield stresses of 690 MPa and 890 MPa respectively were inspected to determine their residual stress distribution using a non-destructive neutron diffraction technique. Details of this neutron diffraction method for measuring residual stresses are presented. It is shown that the technique can achieve high spatial resolution of the residual stresses as well as capturing the high stress gradient in the heat-affected zone, as a consequence of the deep penetration of the neutron particles into the material. The pattern of residual stresses in the specimens reveals that the tensile stresses peak at the flange-web junctions at an average of 70% of the parent material yield stresses, and that the compressive residual stresses have an approximately uniform distribution that dominates large regions of the flange and web. The test results reconfirm the compressive residual stresses being related to the geometry of the cross-section and independent of the steel grade. The interaction of the residual stresses in the flanges and web was found to be negligible for both prismatic and web-tapered beams. A residual stress model applicable for welded thin-walled I-section members for steel grades between 460 MPa and 1000 MPa is proposed by fitting the test results and collective data available in the literature. This representation was incorporated into a detailed finite element (FE) model and it is shown that the FE predictions are in good agreement with the results of experiments conducted on a wide range of HSS I-section beams tested to failure caused by buckling and/or yielding. Highlights: Describes Neutron Diffraction Technique for measuring residual stresses in HSS. HSS beams are both prismatic and tapered. Residual stresses are of a different pattern to column-type sections and are different to mild steel beams. Results incorporated into a finite element formulation.